Subjectivity About Sexual Ethics Among Korean Undergraduate Students Using Q Methodology - Youngrye Park, PhD; Eun Ja Yeun, PhD; Yoon Young Hwang, PhD (Elsevier, 2016)
Purpose: Most undergraduate students are in the phase of gaining mental and physical autonomy from their parents as they expand their worlds. The ways that sexual ethics are established during this time may have an important influence on healthy lifestyles and the maintenance of social order. This study aims to determine a typology of undergraduate students' sexual ethics and the characteristics that compose the types. Methods: Q methodology, which analyzes the subjectivity of each type of attitude, was used. The 44 selected Q statements from 43 participants were classified into the shape of a normal distribution using a 9-point scale. The collected data were analyzed using the PC-QUANL program. Results: The results revealed three discrete groups of students with respect to sexual ethics: traditional absolute purity type, open-minded compromise type, and rational responsibility type. Conclusions: The results of this study indicate that different approaches to educational programs on sexual ethics are recommended for undergraduate students based on the three types studied.